P16 Safety and efficacy of transcatheter PDA occlusion in infants less than 6kgs. (2nd March 2016) - Kang, Sok-Leng; Jivanji, Salim; Mehta, Chetan; Tometzki, Andrew J; Martin, Rob P
Abstract : Background: The technique of transcatheter patent ductus arteriosus (PDA) closure has evolved in the past two decades and is increasingly used in smaller patients. We sought to report a multicentre experience of transcatheter PDA occlusion in infants weighing <6kg. Methods: A multicentre, retrospective analysis of children weighing <6 kg in whom transcatheter PDA occlusion was attempted between January 2004 and December 2014 from 10 tertiary paediatric cardiology units in the UK and Ireland. Results: A total of 361 patients underwent attempted transcatheter PDA closure. The mean weight at catheterization was 4.8 ± 1.0 kg and mean age was 5.7 ± 2.7 months. Successful device closure was achieved in 321(89%) patients without major complication. Device placement was attempted but failed in in 13 cases. Device malposition or embolization post release occurred in the remaining 27 cases. Of these, 11 patients had surgical retrieval of the embolized device and PDA ligation; 6 patients were referred for surgery at a later date after transcatheter retrieval of device and 10 patients had ductal closure with a different device after transcatheter retrieval of the initial device. In the 331 patients who had transcatheter PDA occlusion, 34 had coils and 297 had occluders, including Amplatzer Duct Occluder (ADO) (n = 197); ADO II (n = 51); ADO II Additional Sizes (n = 42); Amplatzer Vascular Plug (n = 6); Occlutech Duct Occluder (n = 1). Complete occlusion was achieved in a 312(94%) patients at either catheterization or last available follow-up. Three of 19 patients had mild residual flow which persisted at less than a year post procedure; but follow up data was not complete in the rest. There were 17 cases of mild left pulmonary artery (LPA) stenosis related to device impingement with velocity >2m/s; 11 of which resolved with time, 5 had persistent mild LPA stenosis at last review with Doppler velocity of 2.5m/s or less; and 1 underwent LPA stenting. Mild aortic obstruction was recognised in 10 patients during catheterisation or on post procedure echocardiogram, 7 of which resolved; one had persistent increased velocity at the arch with no diastolic tail at last review and 2 had incomplete follow up data. Other complications include loss of pulse requiring TPA (n = 5) temporary reduction in pulse requiring heparin infusion (n = 16); bleeding requiring transfusion (n = 2); anaesthesia or airway related (n = 1); small pericardial effusion (n = 1); haemopericardium requiring percutaneous drainage (n = 1); tricuspid valve injury (n = 1); and cerebrovascular event (n = 1). There were 13 deaths in the cohort which were unrelated to the procedure. The causes of death were mainly related to underlying chronic lung disease and pulmonary hypertension. Conclusions: Transcatheteter closure of PDA can be safely accomplished in selected infants who are less than 6 kg despite the manufacturer's recommended weight limit of 6 kg for most ductal occluders. The embolization rate (7%) in this group appeared to be higher than published series in infants >6kg, therefore thorough delineation of ductal anatomy and attention to device selection are vital to the success of the procedure.